Analysis of Germination Curves of Cinchona officinalis L. (Rubiaceae) Using Sigmoidal Mathematical Models. (9th January 2023) - Quiñones-Huatangari, Lenin; Huaccha-Castillo, Annick Estefany; Fernandez-Zarate, Franklin Hitler; Morales-Rojas, Eli; Marrufo-Jiménez, Jenny Del Milagro; Mejía-Córdova, Leslie Lizbeth
Abstract : Seed germination is the fundamental phenomenon that determines the successful growth and development of each plant species, even more so in Cinchona officinalis, which is a forest species that stands out for its medicinal importance. The objective of this work was to determine the best sigmoidal mathematical model describing the germination of C. officinalis . For the germination test, a completely randomized design was used with six treatments and three replicates per treatment; 100° C. officinalis seeds were used per replicate, and 1800 seeds were needed in the trial. Gompertz sigmoidal, logistic, and von Bertalanffy models were used to analyse the germination curves of C. officinalis . The results of these adjustments were analysed based on the graphic representation and statistical criteria (Akaike's value (A I C ), R 2, and R a i 2 ). The results suggest that the Gompertz and logistic models have a better graphic representation, showing values close to those observed, while the von Bertalanffy model shows negative germination values. According to the statistical criteria, the lowest AIC and the highest were obtained. R 2 and R a i 2 with the Gompertz model, followed by the logistic model and von Bertalanffy. It is concluded that the Gompertz model can represent the shape of the germination curves of C. officinalis for the six treatments of the test.